Design and Analysis of Two Wheeler for Armless Differently-Abled Persons by using ANSYS - S.Rajendran, V.Chokkalingam, M. Kumaran, N. Murugesan, D. Loganathan (Mathematical Statistician and Engineering Applications, 2023)
Transportation has become an integral part of people’s day to day life. At certain times, in large countries like India, people are forced to travel long distance from their work place to their place of residence. There are many ways to make transportation easier for the people with disabilities who may wish to drive by themselves as others on the road. People with disabilities in limbs have difficulties in travelling and cannot travel long distances. They use devices such as wheel chair, crutches and artificial limbs for mobility. These however cannot be used for long distance outdoor transportation Therefore, the aim of this project is to design and fabricate „Foot operated system? for armless people. The Foot Operated Steering mechanism is a mechanism controlled by foot or both the feet in order to steer the vehicle in the desired direction. This system consists of a steering which can control brake along with steering. The main objective of the project is to design a foot operated system for handicapped people.